ADVANCEMENTS IN THE THERAPEUTIC APPROACHES TO TREAT NEUROLOGICAL DISORDERS (CAHIERS MAGELLANES-NS, 2024)
As the population ages, neurological problems, particularly neurodegenerative diseases, are becoming more common. The nervous system is a highly specialized and sophisticated network. Our nervous system organizes, explains, and links us to the world around us, from sight to scent, movement to speech. Many key activities in our bodies are controlled by them, including perception, language, memory, movement, swallowing, breathing, and even bowel and bladder function. Understanding neurological disease signs is essential for receiving the proper diagnosis and care. In this book, we have discussed 7 disorders such as multiple system atrophy, cognitive impairment, vascular dementia, traumatic brain injury, epilepsy, schizophrenia, subarachnoid and intracerebral hemorrhage. Their symptoms, pathogenesis, and therapies are discussed.